Levels of Mercury in oil companies and relation of them with the other elements for avoid side effect on the extraction and refining operation and environment - Ali, Najwa Saleem; Mohsen, Hassan Noori; Abd, Khalid Rasheed (Journal of Petroleum Research and Studies, 2019)
For the first time in Iraq, the estimation of the mercury amount in all the establishments of oil mininstry, is stuided in this wrok. It was found that the presence of mercury in the crude oil, theassociated gas, and the associated water as well as in most flare gases. Also, it was observed that the concentration of mercury on the surface of the soil near the flame is increased its concentration in winds of the flame, where most of the days of the year the wind is coming from the north West towards the south-east. The test of mercury has become a global provision to determine its quantity in crude oil and natural gas, which is required the effective ways, led by the Technical Department of the Ministry of Oil to request the petroleum research and development center to determine the amount of mercury in a number of oil companies. This work is proposed by the analytical department of the petroleum research and development center where the cold testing device was imported for the determination of the tiny amount of mercury in gases, liquids and soil and the detection limit in Nano grams. It is the first device operating in the oil sector using for the determination of mercury amount. However, the search results and quantification of mercury, important relationships were identified in terms of the presence of mercury and other crude oil components or tests on crude oil. It was found that there is a correlation between the concentration of mercury and the sulfur content in oil. Mercury is a volatile substance either vapor, dust, or sulfuric. Therefore, the oil gas contains a percentage of mercury, over time, formed by the burning of the gas and the pollution of air and the soil surrounding the flame, which constitutes an environmental hazard that must be avoided in the future. In addition, the accompanying water has a significant content of mercury.